Experience of Medical Disputes, Medical Disturbances, Verbal and Physical Violence, and Burnout Among Physicians in China - Wu, Yinuo; Jiang, Feng; Ma, Jing; Tang, Yi-Lang; Wang, Mingxiao; Liu, Yuanli (Frontiers in Psychology, 2021)
Background Medical disputes, medical disturbances, verbal and physical violence against physicians, and burnout have reached epidemic levels. They may negatively impact both physicians and the healthcare system. The experience of medical disputes, medical disturbances, verbal and physical violence, and burnout and the correlates in physicians working in public hospitals in China needed to be investigated. Methods A nationwide cross-sectional survey study was conducted from 18-31 March 2019. An anonymous online questionnaire was administered. The questionnaire included the 22-item Maslach Burnout Inventory-Human Services Survey (Chinese version). We also collected data on demographic and job-related factors, as well as physicians’ experiences of medical disputes, medical disturbances, verbal and physical violence from patients and the patients’ family members. Findings In total, 22,213 physicians from 144 tertiary public hospitals in all of China’s 31 provinces completed the survey. The overall burnout rate among the surveyed physicians was 31.28%. And 33.48% of physicians experienced disputes, 20.86% experienced disturbances, 48.52% experienced verbal violence, and 5.84% experienced physical violence in the past 12 months. Factors found to be significantly associated with burnout included a younger age, being divorced or widowed, having a lower educational background, working in internal medicine departments, longer working hours per day, working in general hospitals, being in East China, as well as having experienced disputes, disturbances, and physical and verbal violence. Interpretation Close to a third of the Chinse doctors working in the tertiary hospitals reportedly experienced burnout, and the problem is related to the unsafe working environment, caused by the worsening doctor-patient relationship.